Body wave characteristics and variability of an international and a regional level swimmer in 50 m butterfly swimming - Gonjo, T.; Olstad, B. H. (ISBS Proceedings Archive (Michigan), 2020)
The purpose of this study was to compare body wave characteristics between butterfly swimmers with different competitive levels as a case study. An international and a regional level swimmer performed a 50 m butterfly with their maximum effort, and their one stroke cycle velocity, stroke frequency, stroke length, and the vertical coordinate of the shoulder, hip, knee, and ankle joint were quantified for each stroke. The vertical coordinate data were analysed by a Fourier analysis to establish the amplitude, phase angle, contribution to the total signal of harmonic with one maxima/minima (due to one arm stroke motion in a cycle: H1) and two maxima/minima (related to two kicks in a cycle: H2). The velocity of each harmonic travelling caudally between shoulder and hip, hip and knee, and knee and ankle was also obtained. The international swimmer was faster by 23% with 17% longer stroke length and 6% higher stroke frequency than the regional swimmer. The international swimmer was also characterised by lower inter-stroke variability in the amplitude, contribution, and wave velocity of H1 and H2, suggesting that the international swimmer has a more stable rhythm and coordination between the upper and lower body compared with the regional swimmer. The international swimmer had a larger contribution of H1 to the vertical shoulder motion than the regional swimmer, meaning that the kick motion of the international swimmer originates from a more cephalic part of the body compared with the regional swimmer. The international swimmer generated the shoulder H1 rhythm for one stroke cycle at the end of the preceding cycle whereas the regional swimmer produced the shoulder H1 rhythm at the beginning of each cycle, which might be a reason for the higher stroke frequency of the international swimmer compared with the regional swimmer.